Experimental study on the ignition and combustion characteristics of TMEDA and WFNA in hypergolic fuel systems; Acta Astronautica; Vol. 236 - Vysokomornaya O. V. Olga Valeryevna; Pleshko Andrey Olegovich A. O.; Paushkina K. K. Kristina Konstantinovna; Nadymova N. P. Nadezhda Pavlovna; Nigay A. G. Aleksandr Gerasimovich; Glushkov D. O. Dmitry Olegovich (2025, 2025)
Title screen